Réponses

2013-09-18T18:59:37+02:00
23+(-3-6)+(-11)-3) -10+(4+(-18)-(21)-4)
23-9+(-11)-3)-10+(4+(-39-4)
14+(-11)-3) -10+4+(-43)
25-3 -10+(-39)
22-10+(-39=
11+--39)
-28

merci
derient
C'est faut, le resultat doit etre -49
tu pe me le donner le calcul stp
2013-09-18T19:05:29+02:00
23+(-3-(-18+24)+(6-17)-3)-10+(4+(-3-15)-(28-7)-4)
=23-3+18-24+6-17-3-10+4-3-15-28+7-4
=-49
merci
preuve que le réulta = -49
https://www.google.fr/search?q=23%2B(-3-6)%2B(-11)-3)+-10%2B(4%2B(-18)-(21)-4)&oq=23%2B(-3-6)%2B(-11)-3)+-10%2B(4%2B(-18)-(21)-4)&aqs=chrome..69i57j0.1099j0&sourceid=chrome&ie=UTF-8
merci